Burglars Breakfast The (Hb) - Young Rea (3.1 Young Reading Series One (Red) - Everett ,Felicity (Usborne Publishing Ltd, 2007)
An amusing and original story with easy-reading text for children who have just started reading on their own. After a hard night's thieving, Alfie the burglar likes to go home to a tasty meal. But one day he returns to find his cupboards bare. Someone has burgled his breakfast! Part of the Usborne Reading Programme developed with reading experts at the University of Roehampton.